IoT- based recreational area smart street lighting system / Maisarah Mohamad Rahfidi - Mohamad Rahfidi, Maisarah (2019)
Currently, in the whole world, enormous electric energy is consumed by the streetlights. This study explored the feature of Internet of Things (IoT) in addressing the problem of the energy waste in terms of lighting street. Smart street lighting system is a project on intelligent illumination control of streetlights to optimize the problem of power consumption and illumination of the streets. Streetlights today are being replaced by LED street lighting system, which reduces the power consumption. This smart street lighting system consists of LED lights, light sensors, motion sensors and short-distance communication networks. The objective of this thesis is to develop a street lighting system that the intensity of light depends on the location of a person. Furthermore, the purpose is also to design and develop prototype of a smart street lighting system at a recreational area.